Cardiospam: surgical treatment and results - Rubio, Roberto; Xavier, Artigas (Cirugía del Uruguay, 1975)
Since 1970, the authors have claimed for a more aggre¡:;sive management of cardiospesm. preIerrlng UnmerH,qte surgieal treatment. In order to be eftcctive, dllélt&tions must be per!ormed with pneumatlc or bydrosta11c dilators. which means an important risk of esophageal rupture. Furthermore, In 4 to 8 % oí the cases, cerdlospasm. ls associatsd to en esophagus cancer, which, In this situalton, is of a very unfavourable prognosis. The best way to de<:rease its occurrence is to operate palif'.nts with cardiospasm enrlier. In a11 cases they perform. nn extra-mucosal carmomyotomy, aceording to Heller's technique mOdifled, wjth a long, single incission (not shorter than 8 or 10 cm), by thor:.lc!c approach. In 12 treated cases there was not morbimortality on operating. Delaycd results were excelIent in 9 cases and satlsfactory in 3.